ANALISIS MANAJEMEN RISIKO OPERASIONAL PEMBIAYAAN UMKM KSPPS UB AMANAH SYARIAH PADA MASA PANDEMI COVID- 19 - Saragih, Ahmad Ripai; Sugianto, Sugianto (Universitas Islam Negeri Mataram, 2022)
The purpose of this study is to analyze the operational management of SME financing, the risks that arise in the operation of SME financing during the Covid-19 period and the role of risk management in minimizing the operational risk of MSME financing during the COVID-19 pandemic at KSPPS BMT UB Amanah Syariah, Kecamatan Percut Sei. The research approach used in this research is a descriptive qualitative approach. In this study, the researcher used a case study strategy. The reason for using the case study approach, among others, is that research results are difficult to manipulate because this research has little opportunity to control the events to be studied. The result of this research is that the provision of SME financing to KSPPS BMT UB Amanah Syariah has carried out operational risk management during the COVID-19 pandemic on SME financing to minimize operational risks that occurred during the COVID-19 pandemic.